Influence of Malay language on some UUM students use of English: A study of errors and facilitation - Mat Zin, Rasidah; Chulan, Majdah; Ahmad, Badrul Hisham
Many errors that learners of second language make are predictable or even expected. This is a feature of inter-language. The term inter-language was coined by the American linguist, Larry Selinker, in recognition of the fact that second language: learners (L2) construct a linguistic system that draws, in part on the learner’s first language (Ll) and from the target language. A learner’s inter-language is, therefore, a unique linguistic system, thus, no matter how often students are corrected in some aspects of language, they will not get it right until they are cognitively ready.